2013
DOI: 10.1007/s10811-013-0152-y
|View full text |Cite
|
Sign up to set email alerts
|

Unusual distribution of floating seaweeds in the East China Sea in the early spring of 2012

Abstract: Floating seaweeds play important ecological roles in offshore waters. Recently, large amounts of rafting seaweed have been observed in the East China Sea. In early spring, juveniles of commercially important fish such as yellowtail accompany these seaweed rafts. Because the spatial distributions of seaweed rafts in the spring are poorly understood, research cruises were undertaken to investigate them in 2010, 2011, and 2012. Floating seaweed samples collected from the East China Sea during the three surveys co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 34 publications
0
32
2
1
Order By: Relevance
“…The species can be used for alginate production and development of pharmaceuticals (Park et al ., ) as well as a food source for holothurian or abalone aquaculture (Seo et al ., ). Recent research cruises reported that Sargassum beds could be transported to fringe areas of the continental shelf and waters influenced by the KC after they become detached off Zhejiang Province, China (Komatsu et al ., ; Mizuno et al ., ). Phylogeographical studies of the brown algae S. hemiphyllum , S. horneri and S. fusiforme , which comprise the main component of floating Sargassum patches, showed that historical events (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…The species can be used for alginate production and development of pharmaceuticals (Park et al ., ) as well as a food source for holothurian or abalone aquaculture (Seo et al ., ). Recent research cruises reported that Sargassum beds could be transported to fringe areas of the continental shelf and waters influenced by the KC after they become detached off Zhejiang Province, China (Komatsu et al ., ; Mizuno et al ., ). Phylogeographical studies of the brown algae S. hemiphyllum , S. horneri and S. fusiforme , which comprise the main component of floating Sargassum patches, showed that historical events (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…That could be explained by all those disturbances in the ocean environment such as increase in sea temperature, changes in global water cycle, changes in salinity which affect sea currents and marine life. Wind also affects currents which influence the transport and distribution of floating seaweeds according to [30]. These oceanic parameters are linked in such a way that any disturbance to one induces immediate imbalance in the others.…”
Section: Discussionmentioning
confidence: 99%
“…Thalli mature in spring. Dense forests develop on hard substrata, such as bedrock or boulders, surviving from depths of 1–3 m (Umezaki 1984; Komatsu et al 2014). Populations grow down from the surface layer into the subtidal zone, reaching depths >7 m. On the Sanriku coasts of Japan, S. horneri forms stands of thalli that are attached to the bottom to a depth of 7 m and float upward, forming canopies on the sea surface (Komatsu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The thalli have many gas-filled vesicles that provide buoyancy for the floating canopy. Detached thalli float on the surface and often form rafts of tangled seaweed (Komatsu et al 2006). A large number of floating S. horneri rafts occurred in the southern Yellow Sea drifting from south to north (Cai et al 2014), and they were shown by genetic markers to be from Zhejiang province, China and Jiangling, Korea (Chen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation